Analisis Potensi Cadangan Carbon Nekromasa di Hutan Larangan Adat Kenagarian Rumbio Kecamatan Kampar Provinsi Riau - Sri Wulandari; Yuslim Fauziah; Irfan Irfan (Universitas Riau, 2022)
This study aims to determine the potential of carbon stocks based on necromass decomposition in the Hutan Larangan Adat Kenagarian Rumbio Kampar District. The research was conducted from January to March 2020, using the survey method. The selection of the location of the observation station was carried out by purposive random sampling based on 3 conditions of vegetation conditions, namely dense, medium and tenuous. At each station, 10 plots measuring 20x20 meters were made for measuring tree necromass and subplots measuring 1x1 meter long for measuring litter necromass. The results showed that the potential necromass carbon stock in the Kenagarian Rumbio Prohibition Forest was 8.27 tons/ha for tree necromass and 0,13 tons/ha for necromass litter.